Shale oil and gas The promise and the peril - Rao, Vikram (RTI Press Publication, 2015)
In the first edition, Shale Gas: The Promise and the Peril, Vikram Rao explained that shale gas has the potential to transform the U.S. energy-based economy in the electricity, transportation, and chemical sectors. Since then, shale oil burst into the national consciousness even more rapidly than did shale gas. In the second edition, Rao does more justice to the shale oil-related issues, including the consequences of unpreparedness of infrastructure to deliver fluids to market. Six new chapters discuss issues such as chemicals disclosure and challenges to the orthodoxy in the production of fuels and chemicals. Both the first and second editions are intended to inform both sides of the fracturing debate, where currently rhetoric is overtaking understanding. Tailored for a nontechnical audience-with technical chemistry and geology information couched in sidebars-the second edition culminates in suggestions for research and guidance for policy making.